THE ROLE OF PSYCHOLOGY IN MILITARY EDUCATIONAL EDUCATION OF OFFICERS. - Rayimov Sodiq Sobirovich (Scholar Express Journal, 2022)
Today, given the significance of training a future officer in scientific and military circles as a whole person, it is essential for him to independently comprehend his role as a civilian and his intended career, both from the perspective of military art and from that of working with people. It should be emphasized that scientific works and works hardly ever discuss the unique characteristics of the military's educational system. The countries of Russia and Europe are responsible for the majority of the works in this field. Officers will offer their opinions on the place of psychology in military education in this article.
Keywords: Military; Psychology; Upbringing; Officers